Estudo farmacognóstico das folhas de Talinum patens (L.) Willd(Talinaceae) - Reis, Felipe Cunha Dos (2014)
Plants have been used for therapeutic purposes since ancient times, and currently, through studies of safety, efficacy and quality they become possible alternatives as herbal medicines, or through prospective trials, promising sources of molecules prototype drug candidates. In recent years, the emergence of multi-resistant micro-organisms to antimicrobial agents available in medical practice has been the reason for continued concern by the scientific community, directing search for new antimicrobials. Talinum patens (L.) Willd (Talinaceae) is a plant widely used in cooking and for therapeutic purposes in folk medicine. In this context, the objective of this research was to carry out a pharmacognostic study of T. patens, including the evaluation of antibacterial, antifungal, anti-mycobacteria, leishmanicidal and radical scavenger from dry leaves hydroethanolic extract and its fractions: hexane, ethyl acetate, butanol and water. Evaluation of the antimicrobial activity was performed by the methods of agar diffusion and broth microdilution, getting through the minimum inhibitory concentration (MIC). Dried extract showed MIC of 250 and 500 mg/​​ml against Serratia marcescens and Staphylococcus aureus respectively, and the hexane fraction was more effective against Gram-positive bacteria and yeasts with MIC of 31.2 mg /ml for Micrococcus luteus and Candida albicans. Ethyl acetate fraction was active against Gram-negative bacteria with MIC of 31.2 mg/ml for Escherichia coli. In addition, at phytochemical screening, dried extract showed a positive reaction for saponins, steroids and tannins. The hexane fraction showed a positive reaction for steroids and ethyl acetate to saponins and steroids. Therefore, hexane and ethyl acetate fractions from T. patens leaves showed promising antimicrobial activity, being candidates for future studies in research for substances with antimicrobial activity and new drug candidates against Gram-negative and positive bacteria and pathogenic fungi. Additionally, dried extract showed good scavenging activity of DPPH radicals and significant concentration of polyphenols (17.4 mg GAE/g extract). It was proposed by mass spectrometry, as secondary metabolites, the steroids stigmasterol, kaempsterol and b-sitosterol.